Effects of fatigue from sleep deprivation on experimental periodontitis in rats. (12th May 2014) - Nakada, T.; Kato, T.; Numabe, Y.
<x xml:space="preserve">Abstract</x> Background and Objective Factors such as vascularization of the periodontium, inflammatory reactions and immune response affect the oral environment and ecology, decreasing host resistance and promoting the development of symptoms and the advancement of periodontal disease. Fatigue also influences the hypothalamic–pituitary–adrenal axis and reports relate it to systemic resistance. The aim of this study was to evaluate whether fatigue is a modifying factor for periodontal disease in rats. Material and Methods We divided 24 3‐wk‐old male Sprague–Dawley rats randomly into the following four groups: control; fatigue (deep sleep deprivation for 7 d); infection (rats inoculated with carboxymethyl cellulose containing periodontopathic bacteria); and compound (combined fatigue and infection conditions). Weight, serum corticosterone levels, serum albumin levels, interleukin‐1β and tumor necrosis factor‐α expression levels and distance from the cement–enamel junction to the alveolar bone crest were measured at baseline, and on the 36th (before sleep deprivation), 43rd (immediately after sleep deprivation) and 57th d (end of experiment). Results Immediately after sleep deprivation and at the end of the experiment, weight gain in the fatigue and compound groups was significantly lower than in controls (p < 0.05). Immediately after sleep deprivation, serum corticosterone levels were significantly higher in the fatigue and compound groups than in controls (p < 0.05). Moreover, serum albumin levels were significantly lower in the fatigue and compound groups than in controls (p < 0.05). Immediately after sleep deprivation, gene expression of interleukin‐1β was significantly higher in the infection and compound groups than in controls (p < 0.05). Moreover, gene expression of tumor necrosis factor‐α was significantly higher in the compound group than in controls (p < 0.05). At the end of the experiment, the distance from the cement–enamel junction to the alveolar bone crest was significantly higher in the infection and compound groups than in controls (p < 0.05). Moreover, the distance was significantly higher in the compound group than in the infection group. Conclusions Fatigue worsened systemic health in rats and increased gingival inflammation and alveolar bone loss in experimental periodontitis. In conclusion, our results suggest that fatigue is a modifying factor for periodontal disease in rats.